Niche partitioning and trait tradeoff strategies enable plants to coexist under interspecific competition in restored wetlands - Yang, Shenglin; Yuan, Zhen; Ye, Bibi; Zhu, Feng; Tang, Xiaoxian; Gao, Rui; Chu, Zhaosheng; Liu, Xiaowei (Frontiers in Plant Science, 2025)
BackgroundNiche partition and traits tradeoff theory were primary strategies for plants coexistence. However, specific strategies of plants remained to be verified to guide community configuration and biodiversity maintenance in ecological restoration.MethodsThe variation of plants composition and niche breath were utilized to examine the temporal and spatial niche partition strategies, respectively. Meanwhile, the chi-square (χ2), Spearman rank correlation coefficient (rij), Ochiai index (OI) were employed to analyze the interspecific relationship of 30 predominant species from species pool of 220 vascular plants. Besides, the Lotka-Volterra model was utilized to reveal the traits tradeoff strategies of predominant species from five vegetation formations.ResultsAbout 62.41% pairs of wetland species were niche partitioned while 37.58% of species pairs were niche overlapped. In temporal scale, 60.5% of species occurred either in spring or autumn while 39.5% occurred in both seasons. Meanwhile, significant change of relative height (RH) and relative coverage (RC) were observed in constructive species and auxiliary species. Height tradeoff strategy (ΔRHΔRC>1), coverage enlarge strategy (ΔRHΔRC<1), or both strategies (ΔRHΔRC=1) observed in wetland plants.DiscussionOur finding testified that the temporal niche partition and traits tradeoff strategies are objectively observable in wetland plants. These findings on coexistence strategies can be used in the configuration of plants communities and the biological control of alien invasive plants.